Immune checkpoint inhibitor induced myocarditis, myasthenia gravis, and myositis: A single‐center case series - Joshua Longinow; Mohammad Zmaili; Warren Skoza; Nicholas Kondoleon; Robert Marquardt; Cassandra Calabrese; Pauline Funchain; Rohit Moudgil (Cancer Medicine)
Abstract Background Immune checkpoint inhibitors can result in overlap syndrome comprised of myasthenia gravis, myositis and myocarditis. However, the mortality predictors have not been clearly delineated. Methods We examined the characteristics of 11 patients diagnosed with overlap syndrome at Cleveland Clinic. All the available clinical, diagnostic, biochemical and disease specific factors were examined. Clinical predictors of increased mortality were using student t‐test for parametric data and Wilcoxon‐signed rank testing for nonparametric data. Results Seven patients out of eleven patients were alive during the analysis. Our study did confirm that troponins were indicator of early demise. However, study showed that elevated creatinine, BUN, and decreased hemoglobin were also observed in patients who met early demise. Unlike previously published studies, elevated NT Pro‐BNP and reduced left ventricular ejection fraction were not a seen in this study. However, there were higher incidence of electrical abnormalities in deceased patients when compared to alive. Conclusion Our study is first to examine various clinical parameters of overlap syndrome that might be predictive of mortality. This study confirms troponin as possible predictor and adds elevated creatinine, BUN and reduced hemoglobin as possible early biomarkers in deceased patients. The analysis showed that reduced LVEF was not a seen in deceased patients.